IMPROVING THE INSTITUTION OF IAIN TULUNGAGUNG THROUGH CREATING NEW INNOVATION - Chotimah, Chusnul (IAIN Tulungagung, 2019)
The institutional development can be done by any strategies, one of them are creating new innovation called as blue ocean strategy. Blue ocean strategy is theway to develops the institution without had to quarrel in the strict zone with another institution. Its different with red zone strategy determining the birth of new market space or different innovation has been owned. So, this strategy is more emphasize how the institutions have not to conquer the competition using the vis á vis to the rival. The study of this article is about using Blue ocean strategy at public relation in developing the institution since the beginning the statuses change of STAIN Tulungagung to IAIN Tulungagung, 2013. This paper approaches qualitative research which is focused on the strategy of developing IAIN Tulungagung institution through the new innovation: creating of the value innovation, recruiting new students intensively established the out of box edu-fair event, branding, establishing the advance program and promoting the institution, developing the human capital. All of those new innovations are blue ocean strategy has been done by IAIN Tulungagung according to different four steps of work scheme profits such as Decrease-Delete-Create-Increase becomes Passive-Save-Create-Increase.